PENGARUH PENGAWASAN DAN STRES KERJA TERHADAP KEPUASAN KERJA PARAMEDIS RUMAH SAKITAZ–ZAHRA KECAMATAN UJUNGBATU KABUPATEN ROKAN HULU - , Arwinence Pramadewi, Agustina Ria Lestari , Zulfadil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of Supervision and Job Stress on Job Satisfaction of Paramedics at Az–Zahra Hospital, Ujungbatu District, Rokan Hulu Regency. The population in this study were all employees working at Az-Zahra Hospital Ujungbatu, totaling 78 people. In this study, the sample used was 30 samples of paramedical employees. Sampling used a purposive sampling method. The primary data in this study were obtained through interviews and distributing questionnaires to prove the research results. The hypothesis testing in this study was using multiple linear analysis with the help of the SPSS program. The results showed that: 1) partial job supervision had a significant effect on paramedics' job satisfaction in hospitals, 2) partial work stress had no significant effect on paramedics' job satisfaction in hospitals, 3) supervision and work stress had a joint effect significant effect on paramedic job satisfaction. Keywords: Supervision, Job Stress, Job Satisfaction